EFFECTIVENESS OF INFLIXIMAB IN PATIENTS WITH JUVENILE ANKYLOSING SPONDYLARTHRITIS - A.L. Kozlova; E.I. Alexeeva; S.I. Valieva; T.M. Bzarova; A.M. Chomakhidze; K.B. Isaeva; R.V. Denisova; E.Yu. Gudkova; A.O. Lisitsin ("Paediatrician" Publishers LLC, 2009)
The objective of open-labeled study was estimation of effectiveness and safety of infliximab - monoclonal antibodies to tumor necrosis factor (TNF) - in treatment of 48 patients with juvenile ankylosing spondylarthritis. Duration of observation was 6 weeks - 1,5 years. Anticytokine treatment was administrated on the ground of therapy with immunosuppressive agents in 96% of patients. Infliximab was administrated in median dose 7,4 ± 3,7 mg/kg of body weight by standard scheme (0-2-6 - week and further every 8 weeks) intravenously. Results of a trial showed that infliximab has evident anti-inflammatory effect. Treatment with infliximab provided development of remission of articular syndrome, decreasing and normalization of laboratory indices of activity of disease, the rate of disability, and increasing of quality of life in 84% of patients. Effect of this medication was registered after first infusion and continued during all period of follow up. Adverse effects included transfusion reactions: fever, head ache, nausea/vomiting in 10% of patients, allergic arthritis - in 2% of patients. Thus, treatment of infliximab is pathogenetically grounded, effective and safe in patients with juvenile ankylosing spondylarthritis. Key words: children, juvenile ankylosing spondylarthritis, infliximab, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(2):20-26)